Verbal Bullying and game: A religious and ethical dilemma - Brastama, Alverelleon Jasca (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
The issue on verbal bullying in online games, particularly in Valorant, raises significant ethical and moral concerns that resonate with broader religious and ethical dilemmas. The study highlights the issue of verbal aggression and cyberbullying, which can lead to emotional distress and harm among players. This mirrors the ethical dilemma of promoting kindness and respect in online interactions, a principle often emphasized in various religious traditions. The anonymity provided by the chat feature in games exacerbates the problem, echoing the concept of accountability and responsibility in religious teachings. The study's recommendation for a multifaceted approach involving increased moderation, player education, and mental health support aligns with the ethical imperative to protect and care for one another, a fundamental principle in many religious and moral frameworks. By addressing these issues, the gaming industry can foster a more inclusive and respectful environment, reflecting the values of compassion and empathy that are central to many religious and ethical traditions.